Communal coping and its association with marital relations and psychological outcomes among healthcare professionals during the COVID-19 pandemic - Alimoradi, Zainab; Soleimani, Mohammad Ali; Keramtkar, Maryam; Bahrami, Nasim; Griffiths, Mark D. (Frontiers in Psychology, 2022)
Background: Communal coping is a type of interdependency in which couples dealing with a health threat share assessment of a threat and respond together to the stress. The present study investigated communal coping with the COVID-19 pandemic and its association with psychological and relational outcomes among healthcare professionals. Methods: In the present cross-sectional survey study, 242 healthcare professionals from hospitals and health centers were recruited via convenience sampling between August and October 2020. Communal coping with working conditions during the COVID-19 pandemic, dyadic adjustment, psychological distress, and fear of COVID-19 along with demographic and professional characteristics were assessed via an online survey. Results: Multi-variable linear regression showed that dyadic adjustment (β = 0.73), psychological distress (β = 0.16), fear of COVID-19 (β = 0.11) and support gap (β = -0.04) were significant independent variables associated with communal coping among healthcare professionals. Conclusion: Healthcare professionals coped communally within the family in dealing with working conditions during the COVID-19 pandemic. Dyadic adjustment was the strongest predictor of communal coping among healthcare professionals.